Symmetry broken vectorial Kerr frequency combs from Fabry-Pérot resonators - Hill, Lewis; Hirmer, Eva Maria; Campbell, Graeme; Bi, Toby; Ghosh, Alekhya; Del’Haye, Pascal; Oppo, Gian Luca (Communications Physics, 2024)
Spontaneous symmetry breaking of a pair of vector temporal cavity solitons has been established as a paradigm to modulate optical frequency combs, and finds many applications in metrology, frequency standards, communications, and photonic devices. While this phenomenon has successfully been observed in Kerr ring resonators, the counterpart exploiting linear Fabry-Pérot cavities is still unexplored. Here, we consider field polarization properties and describe a vector comb generation through the spontaneous symmetry breaking of temporal cavity solitons within coherently driven, passive, Fabry-Pérot cavities with Kerr nonlinearity. Global coupling effects due to the interactions of counter-propagating light restrict the maximum number of soliton pairs within the cavity - even down to a single soliton pair - and force long range polarization conformity in trains of vector solitons.
CRIS-Team Scopus Importer:2024-03-15